Mononuclear myeloid-derived “suppressor” cells express RAE-1 and activate natural killer cells - Nausch, Norman (American Society of Hematology, 2008)
Myeloid-derived suppressor cells (MDSCs) accumulate in cancer patients and tumor-bearing mice and potently suppress T-cell activation. In this study, we investigated whether MDSCs regu-late natural killer (NK)–cell function. We discovered that mononuclear Gr-1(+)CD11b(+)F4/80(+) MDSCs isolated from RMA-S tumor-bearing mice do not suppress, but activate NK cells to produce high amounts of IFN-γ. Gr-1(+)CD11b(+)F4/80(+) MDSCs isolated from tumor-bearing mice, but not myeloid cells from naive mice, expressed the ligand for the activating receptor NKG2D, RAE-1. NK-cell activation by MDSCs depended partially on the interaction of NKG2D on NK cells with RAE-1 on MDSCs. NK cells eliminated Gr-1(+)CD11b(+)F4/80(+) MDSCs in vitro and upon adoptive transfer in vivo. Finally, depletion of Gr-1(+) cells that comprise MDSCs confirmed their protective role against the NK-sensitive RMA-S lymphoma in vivo. Our study reveals that MDSCs do not suppress all aspects of antitumor immune responses and defines a novel, unexpected activating role of MDSCs on NK cells. Thus, our results have great impact on the design of immune therapies against cancer aiming at the manipulation of MDSCs.